Design and discovery of 2-(4-(1H-tetrazol-5-yl)-1H-pyrazol-1-yl)-4-(4-phenyl)thiazole derivatives as cardiotonic agents via inhibition of PDE3. Issue 18 (15th September 2015) - Duan, Li-Min; Yu, Hong-Ying; Li, Yan-Long; Jia, Chun-Juan
Graphical abstract: Highlights: Compound6d exhibited most potent inhibition of PDE3A than PDE3B. It buried deep inside the PDE pocket lined with residues like Tyr737, Phe559 and Phe991. It shows no observational changes, morbidity and mortality in experimental animals in toxicity assay. Abstract: A series of novel 2-(4-(1 H -tetrazol-5-yl)-1 H -pyrazol-1-yl)-4-(4-phenyl)thiazole derivatives, 6 (a –o ) were designed, synthesized and evaluated for inhibitory activity against human PDE3A and PDE3B. In PDE3 assay, entire set of targeted analogs showed considerable inhibition of PDE3A (IC50 = 0.24 ± 0.06–16.42 ± 0.14 μM) over PDE3B (IC50 = 2.34 ± 0.13–28.02 ± 0.03 μM). Among the synthesized derivatives, compound6d exhibited most potent inhibition of PDE3A with IC50 = 0.24 ± 0.06 μM than PDE3B (IC50 = 2.34 ± 0.13 μM). This compound was further subjected for evaluation of cardiotonic activity (contractile and chronotropic effects) in comparison with Vesnarinone. Results showed that, it selectively modulates the force of contraction (63% ± 5) rather than frequency rate (23% ± 2) at 100 μM. Docking study of above compound was also carried out in the active site of PDE3 protein model to give proof to the mechanism of action of designed inhibitor. Further, in sub-acute toxicity experiment in Swiss-albino mice, it was found to be non-toxic up to 100 mg/kg dose for 28 days.